How can the usage of data analytics help football clubs create a competitive advantage: a research on Liverpool football club - Pinto, Bernardo Baptista Da Costa (2021)
Given the huge complexity of the sport, clubs need to seek for contemporary approaches to the usage of data to improve the club’s overall performance. The purpose of this thesis is to understand how data science is shaping the decision-making of football clubs and how can clubs leverage on the power of data to gain a competitive edge in an extremely challenging industry. Further analysis on Liverpool F.C. suggests that indeed data analytics had an impact in its successful stride for silverware, with notorious improvements both sportingly and financially, however this might have been influenced by other factors.